2015
DOI: 10.1007/s00253-015-7208-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of highly alkaline conditions to improve cost-effectiveness of algal biotechnology

Abstract: Phototrophic microorganisms have been proposed as an alternative to capture carbon dioxide (CO2) and to produce biofuels and other valuable products. Low CO2 absorption rates, low volumetric productivities, and inefficient downstream processing, however, currently make algal biotechnology highly energy intensive, expensive, and not economically competitive to produce biofuels. This mini-review summarizes advances made regarding the cultivation of phototrophic microorganisms at highly alkaline conditions, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…High volumetric productivities were observed for a mixed microbial community dominated by a cyanobacterium closely related to P. kuetzingianum (maximum 1022 g m −3  day −1 , average 862.91 g m −3  day −1 ) grown at pH 9, 0.5 mol L −1 total carbonates and 80 µmol photon m −2  day −1 . This high productivity combined with the predicted fourfold lower cost of a high pH, high alkalinity system [9] has the potential to reduce the overall cost of phototrophic carbon capture systems. Fatty acid content and profiles were consistent with previously reported axenic cultures of cyanobacteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High volumetric productivities were observed for a mixed microbial community dominated by a cyanobacterium closely related to P. kuetzingianum (maximum 1022 g m −3  day −1 , average 862.91 g m −3  day −1 ) grown at pH 9, 0.5 mol L −1 total carbonates and 80 µmol photon m −2  day −1 . This high productivity combined with the predicted fourfold lower cost of a high pH, high alkalinity system [9] has the potential to reduce the overall cost of phototrophic carbon capture systems. Fatty acid content and profiles were consistent with previously reported axenic cultures of cyanobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Studies haves shown that the cost of carbon dioxide supply can constitute approximately 50% of the cost of biomass production in raceway pond systems [8]. The use of high pH and alkalinity can improve transfer of CO 2 into the culture medium and uncouples CO 2 absorption and biological uptake, leading to lower energy requirements and costs [911]. Haloalkaliphilic eukaryotic algae and cyanobacteria can use bicarbonate instead of CO 2 at high pH [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with only 400 ppm carbon dioxide in air, such direct capture of CO 2 from air would lead to excessive energy costs and evaporation (Davis, Aden, & Pienkos, 2011). The ability of such media to dissolve a large amount of carbon dioxide as bicarbonate, would also enable implementation of CO 2 capture and growth as two separate unit operations (Sharp, Canon-Rubio, Strous, Bergerson, & De la Hoz Siegler, 2015;van Loosdrecht, Daelman, Strous, Sorokin, & Kruse, 2016), saving costs and energy. Alternatively, as previously proposed, we could avoid an energy-expensive concentration step by using growth media with high pH and alkalinity.…”
Section: Introductionmentioning
confidence: 99%